2017
DOI: 10.1177/0735633117708313
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Language Teachers’ Perceptions of Technology and Instructional Use of Technology: A Path Analysis

Abstract: This study examined internal and external factors affecting pedagogical use of technology among 47 K-12 Chinese language teachers in the United States. Path analysis of the survey data was used to examine the relationships between the teachers' instructional use of technology, on the one hand, and on the other, their perceptions of three internal factors (i.e., technology's usefulness, its ease of use, and subjective norms) and one external factor (i.e., facilitating conditions). The results showed that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
2
17
0
2
Order By: Relevance
“…Performance expectation, facilitating conditions, disciplinary factors, institutional policies and availability of support influence the use of ICT (Muriithi et al, 2016). Facilitating conditions are significantly imperative than perceived usefulness and subjective norm in influencing use of technology among teachers (Liu et al, 2018). Research conducted to ascertain relationship between ICT adoption and the classroom experience showed that faculty-perceived usefulness and ease to use influence the ability to harness ICT tools to generate marvellous class-room experience (Salas, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Performance expectation, facilitating conditions, disciplinary factors, institutional policies and availability of support influence the use of ICT (Muriithi et al, 2016). Facilitating conditions are significantly imperative than perceived usefulness and subjective norm in influencing use of technology among teachers (Liu et al, 2018). Research conducted to ascertain relationship between ICT adoption and the classroom experience showed that faculty-perceived usefulness and ease to use influence the ability to harness ICT tools to generate marvellous class-room experience (Salas, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Asnawi, Qismullah, and Rena (2018) studied 26 English teachers in Banda Aceh, and found that they perceived ICT as helpful in teaching. Finally, Liu, Lin, Zhang, and Zheng (2017) used a path analysis to conjecture that teachers' perception of technology could be predicted by perceived usefulness, subjective norms, and facilitating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also revealed that access to technology and resources influences the use of technology and impacts the success of classroom practice (Sadaf & Johnson, 2017;Garling, 2016;Choy et al, 2009;Wright & Wilson, 2006). Meanwhile, it was found that the lack of financing, facilities, infrastructure, and digital content is one of the reasons for the lack of technology integration in teaching (Aşik et al, 2019;Magen-Nagar & Firstater, 2019;O'Neal, Gibson & Cotten, 2017;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%